Flexural behaviour of reinforced concrete beams with partial replacements of metakaolin and marble powder. (2021) - Rajkumar, R.; Umamaheswari, N.; Kumar, Abhishek; Kumar, Mrinal; Vineeth Gupta, L.R.; Pandey, Raoshan
Abstract: Concrete is the most widely used and versatile building material which is generally used to resist compressive force. By addition of some pozzolanic materials as admixtures, the various properties of concrete can be improved. Many modern concrete mixes are modified with the addition of admixtures, which improve the micro structural properties as well as decrease the calcium hydroxide concentration by consuming it through a pozzolanic reaction. Metakaolin is a cementitious pozzolanic material highly efficient and can react rapidly with the excess calcium hydroxide resulting from OPC hydration by a pozzolanic reaction, to produce calcium silicate hydrate and calcium alumino silicate hydrates. Due to rapid growth of construction activity, the available sources of natural sand are getting exhausted. Therefore, it is necessary to replace natural sand in concrete by an alternate material either partially or completely without compromising the quality of concrete. Waste marble dust is one such material which can be used to replace sand as fine aggregate in concrete. The present study describes an experimental program conducted to investigate the flexural behaviour of Reinforced Concrete beams with metakaolin as partial replacement for cement and marble powder as partial replacement for river sand in preparation of concrete. The percentage replacement of cement by metakaolin considered in this experimental study are 0, 2, 4, 6 and 8% by weight of cement and sand by marble powder are 20, 15, 10, 5 and 0%. The mechanical properties such as compressive and split tensile strength are analysed for conventional and modified concretes, at the age of 7, 14 and 28 days. A total of five RC beams, with dimensions 150 × 200 × 1500 mm was cast and tested under four point loading. The observations made were initial crack load, ultimate failure load and deflection of the beams. The results show that metakaolin and marble powder can be used as alternate construction materials at lower percentage replacement levels.